Conservation and molecular characterisation of Irish veteran oak (Quercus spp.) and ash (Fraxinus excelsior L.) - Gallagher, Evelyn (Trinity College (Dublin, Ireland). Department of Botany, 2009)
Three chloroplast markers and three nuclear microsatellite markers were applied to DNA samples from ash-leaf material. Less diversity was found in veteran ash than in the younger populations studied by Harboume et al (2005). Chloroplast DNA haplotypes were compiled and only five out of 15 haplotypes previously found in Ireland were present. Haplotypes were analysed by UPGMA but no biogeographical patterns were discernible, either when the haplotypes or UPGMA groupings were mapped. AMOVA analysis of the chloroplast markers indicated that 57% of the variation was partitioned within populations. The results from genotyping with the three nuclear microsatellites showed similar allele numbers and gene diversities were found in both the present study and Harboume et al (2005). Populations were grouped according to UPGMA, and AMOVA results from analysis of these groupings indicated very little among-population structuring (FST 0.040).
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin